TANGGAPAN PENGUNJUNG TERHADAP OBJEK WISATA MANGROVE RAWA MEKAR JAYA DI KABUPATEN SIAK - Putri Permata Sari; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tourism Object of Mangrove Rawa Mekar Jaya is one of the Ecotourism which has quite good facilities in Siak Regency. However, Infrastructure towards the Object is less supportive. Therefore, this study aims to determine (1) General Description to Tourism Objects of Mangrove Rawa Mekar Jaya (2) Visitor Responses to Tourism Objects of Mangrove Rawa Mekar Jaya. This research uses quantitative descriptive method. The subject of this research was the Rawa Mekar Jaya Mangrove of Tourism Visitor. Data collection techniques used are questionnaires, observation, documentation, and interviews. The results showed that theTourism Object ofMangrove Rawa Mekar Jaya was located in Rawa Mekar Jaya Village, Sei Apit District, Siak Regency. The Tourism Object of Mangrove Rawa Mekar Jaya was established by the Mangrove Natural Home Tourism Awareness Group with an area of 25 hectares. Visitor Responses to Attractions/Tourist Attraction and Facilities on Mangrove Rawa Mekar Jaya Forest Attractions are in good category. However, the visitor's response to the infrastructure towards the Rawa Mekar Jaya Mangrove Forest Tourism Object is still in enough category. To get there there are many roads that are hollow and dusty. And visitors find it difficult to find public transportation facilities that can be used.Keywords : Visitor’s Response, Tourism Object, Mangrove Rawa Mekar Jaya